Proline Reduction and Increasing Growth of Vanilla Plants Induced by BNR Fungus with Dose of Goat Manure and Husk Charcoal - Haryuni Haryuni; Muhamad Amin; Endang Suprapti; Tyas Soemarah Kurnia Dewi; Eko Hartoyo (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Goat manure and husk charcoal are agricultural wastes that have not been used optimally, contain soil microorganisms that are effective in converting nutrients into more perfect forms, play a role in improving soil physical properties and increase the ability of soil to bind nutrients. The purpose of this study is to determine the effect of goat manure and husk charcoal to proline reduction and increase growth of vanilla plant induced by Binucleate Rhizoctonia (BNR). The study was designed with a factorial completely randomized block design. The first factor is the dose of manure (0,5,10,15) g/plant, the second factor is the dose of husk charcoal (0,5, 10, 15) g/plant. Data were analyzed by analysis of variance ANOVA with Duncan's Multiple Distance Test (DMRT) with a significant difference of 5%. The effect of doses of goat manure and husk charcoal induced by BNR can reduce proline contents and increase growth of vanilla plant. The benefit of this research is to provide treatment information to reduce proline levels and increase plant growth with the application of goat fertilizer and husk charcoal.